Międzynarodowe przepływy siły roboczej - Kacperska, Elżbieta (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2016)
The aim of the study is to present the trends in international flows of labor and to identify their causes and consequences in the years 2000–2014.The research involved the migration of population: globally, by region and by immigration and emigration. The research is based on the scientific literature as well as descriptive and comparative analysis. International flows of labour were booming in recent years. In 2015, about 4% of the world’s population migrated. Among the causes of this growing phenomenon, the economic aspect is the most important one (labour migration). The target areas for immigrants are mainly the countries of Western Europe (Germany, France) and North America (USA).